Urea cycle gene expression is suppressed by PFOA treatment in rats - Walters, M.W.; Wallace, K.B. (Toxicology letters, 2010)
Perfluorooctanoic acid (PFOA), with an array of industrial uses, is one of the most common perfluoroalkyl acids. Resistance to biological degradation and a global distribution are characteristics that have caused PFOA to become a frequent subject of toxicological studies. PFOA treatment in rodents causes peroxisome proliferation, mitochondrial biogenesis, and transactivation of PPARs. Prior work has shown urea cycle gene expression to be reduced in mice by another PPARα ligand, WY14643. In light of these findings, the aim of our investigation was to determine if PFOA treatment in rats alters expression of genes responsible for ureogenesis. 30 mg/kg of PFOA was administered to adult male Sprague–Dawley rats via oral gavage for 28 days and their livers were harvested. Gene transcription was measured using real time PCR and protein expression was determined through western blotting. We observed a decrease in mRNA for the coordinately expressed urea cycle genes Cps1, Ass1, and Asl; mRNA of the ammonia generating Gls2 was also reduced. Protein amounts for CPS1, ASS1, and OTC were all decreased in the PFOA treated rats, and interestingly there was an increase in the amount of S133 phosphorylated CREB, which is a regulator of urea cycle gene transcription. We conclude that the transactivation of PPARα by PFOA leads to a metabolic shift that favors the catabolism of lipids over proteins, thereby suppressing urea cycle gene expression. Our findings provide further evidence of the effect of PFOA on intermediary metabolism in rodents and add valuable information in assessing the potential risks of PFOA exposure.